احادیث نبویہ میں وارد بعض حیوانات کا ترجمہ: ایک ناقدانہ جائزہ - ڈاکٹر محمد فیضان الرحمن (FIKR-O NAZAR فکر ونظر, 2014)
Rendering the meanings of a language to another one is a task surrounded by a series of difficulties that grow more complex if both or one of the languages bear the words carrying various dimensions, Arabic for example. Lexicons and the dictionaries make the task easy but still the problems remain unsolved in translating the names of animals. While focusing on the hadith dictionaries, the article shows that how ambiguous definitions of animals, in the absence of their figures, have led to the wrong renderings of words into the Urdu language. In this regard the author argues for the revision and correction of already Urdu translations of Arabic books.